2019
DOI: 10.1002/bkcs.11929
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Homoserine Dehydrogenase from Pseudomonas aeruginosa

Abstract: Homoserine dehydrogenase (HSD) catalyzes the reduction of l‐aspatate‐4‐semaldehyde (l‐ASA) to l‐homoserine (l‐HSE) or oxidation reversely, which is a part of the aspartate pathway synthesizing threonine, isoleucine, and methionine in vivo. HSD has gained much interest in medical application since HSD is a well‐established target for pesticides and antibiotics. In addition, HSD is also valuable in industrial application for l‐lysine production. In this study, HSD from Pseudomonas aeruginosa (PaHSD) was overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In this study, we observed that glutamate 5-kinase (ATG93720), which is involved in glutamate synthesis, was more abundant in the wild-type than in the mutant. In biochemical pathways, glutamates are converted to aspartates, which, in turn, can be degraded to homoserine by homoserine dehydrogenase; the homoserines can be further converted to methionine and threonine ( Kim et al, 2020a ). Based upon our data, the enzymes necessary for the above-mentioned biochemical pathways, homoserine dehydrogenase (ATG95108), threonine synthase (ATG95107), and methionine synthase (ATG95998), are more abundant in the wild-type than in the mutant.…”
mentioning
confidence: 99%
“…In this study, we observed that glutamate 5-kinase (ATG93720), which is involved in glutamate synthesis, was more abundant in the wild-type than in the mutant. In biochemical pathways, glutamates are converted to aspartates, which, in turn, can be degraded to homoserine by homoserine dehydrogenase; the homoserines can be further converted to methionine and threonine ( Kim et al, 2020a ). Based upon our data, the enzymes necessary for the above-mentioned biochemical pathways, homoserine dehydrogenase (ATG95108), threonine synthase (ATG95107), and methionine synthase (ATG95998), are more abundant in the wild-type than in the mutant.…”
mentioning
confidence: 99%